The spatial structure of lithic landscapes: the Late Holocene record of East-Central Argentina as a case study - Barrientos, Gustavo (2014)
The aim of this paper is to discuss conceptual and methodological issues related with the archaeological study of lithic landscapes and exemplify the approach with a case study (artifact distribution data from east-central Argentina). A lithic landscape—understood as the co-occurrence, in a given geographic space, of different structural units each one composed by a raw material source and the complete set of unmodified and human-modified pieces of rock extracted from that source and then transported, used, and discarded across the landscape (i.e., a scatter area)—can be modeled using kriging, a geostatistical interpolation tool useful for integrating scattered information into coherent spatial models. The case study allows for the examination and discussion of, on one hand, the relationships between the type and location of the sources and the size and shape of the respective scatter areas and, on the other, the reciprocal relationships between different raw materials and sources. It is concluded that a proper description of the spatial structure of a lithic landscape is the needed baseline from which to evaluate different explanatory models. Such models should take into account different sets of initial conditions and generative mechanisms, in order to cope with the pervasive problem of equifinality.